PENERAPAN ALGORITMA TURBO BOYER MOORE DALAM SISTEM PENCARIAN DATA KONSUMEN ASTRA MOTOR CABANG BENGKULU - Novperan Nando (Penerbit Jurnal Indonesia, 2022)
The process of managing consumer data and motorcycle sales data has utilized an office application package, namely Microsoft Excel. However, the data collection takes quite a long time, because it has to record all available motorbikes including frame numbers, engine numbers, and dealers who sell these motorbikes, besides that it is difficult to search consumer data. The consumer data search system for Astra Motor Bengkulu Branch is an application that can be used to help manage data on dealers, motorcycles, consumers, motorcycle sales, and facilitate the search for consumer data. This consumer data search system has implemented the Turbo Boyer Moore method which helps facilitate the process of searching for consumer data based on consumer names through character shifts. The consumer data retrieval system for Astra Motor Bengkulu Branch was created using the Visual Basic. Net programming language and SQL Server database. Based on test data conducted with the keyword Man to search for consumer names, the search system automatically conducts research data on the database using Turbo Boyer Moore Method and produces searches on the 5th pattern index. Based on the tests that have been carried out, the functionality of the consumer data search system for Astra Motor Bengkulu Branch has been running according to the design and there are no errors in the application